Feasibility Study of Chicken Slaughterhouse Business Investment - Srimi Ayu Lestari; Mochamad Reza Adiyanto; Bambang Sudarsono; Eni Sri Rahayuningsih (Maro: Jurnal Ekonomi Syariah dan Bisnis, 2023)
This research aims to analyze the feasibility of investing in a Poultry Slaughterhouse business at CV Rafika Foods Indonesia from a financial aspect. This research uses a quantitative method with purposive sampling. The investment feasibility analysis tools used are Net Present Value, Internal Rate of Return, Average Rate of Return, Profitability Index, Break Event Point, Payback Period, Discounted Cash Flow, and Shutdown Point. The data obtained is primary data using interview techniques directly at the place of business. The calculations carried out resulted in a positive Net Present Value of IDR 16,098,182,271 and it was declared feasible. The result of the Internal Rate of Return of 358.120% was said to be feasible because it was greater than the Discount Rate. The Average Rate of Return of 958% was said to be feasible because it was more than 0%, the Profitability Index produces a calculation of 11.73 which is declared feasible because it is more than 1, Break Event Point on income of IDR 7,077,120,000 per year with a payback period of 1 year 1 month 13 days. Discounted Cash Flow calculation of IDR 21,360,209,670 and the results of the Shutdown Point analysis of the CV Rafika Foods Indonesia business with revenues of IDR 58,976,744,186 per year.